Avaliação de parâmetros cardiovasculares fisiológicos utilizando-se Betametasona e/ou Diazepam como medicação pré-operatória em cirurgia de terceiros molares inclusos - Moreira, Tariza Gallicchio (2011)
Impacted third molar surgery is the most performed procedure by the oral facial surgeons and it has been a model for experimentation of various drug therapy protocols. The use of corticosteroids during oral surgeries have been evaluated the anti-inflammatory action. However, there are no published studies that evaluate the physiological features of the use of these drugs in Dentistry. The aim of this study is to evaluate, during the surgery, the cardiovascular parameters influence when betamethasone are used as preoperative therapy for the impacted tooth extraction, analyzing patients who used diazepam or not to control anxiety. A randomized double-blind study was made including 27 patients with no systemic alteration, who were divided into 4 groups, which received single dose of oral preoperative drugs and underwent surgery under local anesthesia. It was observed that betamethasone oral administration before ambulatorial surgery procedures is a safe and effective method to control anxiety, and keeps the cardiovascular parameters within the values. A single dose oral administrated of Betamethasone increases cardiac frequency and diastolic blood pressure during surgery and postoperative period, and the association betamethasone and diazepam significantly reduces these parameters compared to the betamethasone isolated group.